2004
DOI: 10.1037/0882-7974.19.3.495
|View full text |Cite
|
Sign up to set email alerts
|

Explicit and Implicit Stereotype Activation Effects on Memory: Do Age and Awareness Moderate the Impact of Priming?

Abstract: Two studies examined the effects of implicit and explicit priming of aging stereotypes. Implicit primes had a significant effect on older adults' memory, with positive primes associated with greater recall than negative primes. With explicit primes, older adults were able to counteract the impact of negative stereotypes when the cues were relatively subtle, but blatant stereotype primes suppressed performance regardless of prime type. No priming effects under either presentation condition were obtained for you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
167
1
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(190 citation statements)
references
References 43 publications
19
167
1
3
Order By: Relevance
“…Using a similar procedure, Stein, Blanchard-Fields, and Hertzog (2002) replicated these results only partially. Hess et al (2004), however, did replicate Levy's basic findings in two separate experiments using a memory test more typical of those used in studies of cognitive aging (e.g., free recall of a list of words). Hess et al (2004) hypothesized that stereotype activation effects on performance might be most powerful on tasks with a strong strategic component, perhaps explaining the inconsistency across studies.…”
Section: Ideomotor Processessupporting
confidence: 52%
See 1 more Smart Citation
“…Using a similar procedure, Stein, Blanchard-Fields, and Hertzog (2002) replicated these results only partially. Hess et al (2004), however, did replicate Levy's basic findings in two separate experiments using a memory test more typical of those used in studies of cognitive aging (e.g., free recall of a list of words). Hess et al (2004) hypothesized that stereotype activation effects on performance might be most powerful on tasks with a strong strategic component, perhaps explaining the inconsistency across studies.…”
Section: Ideomotor Processessupporting
confidence: 52%
“…Simple awareness that the stereotype has been activated has been associated with attitude suppression or nonconsistent behavior (e.g., Hess et al, 2004;Lepore & Brown, 2002). In addition, individual characteristics, such as the extent to which one values a stereotyped behavior (e.g., or concerns about one's group being stigmatized (e.g., Brown & Pinel, 2003), can moderate the impact of stereotypes.…”
Section: Ideomotor Processesmentioning
confidence: 99%
“…Other reviews, such as Hess et al [18], found that research on implicit stereotypes has shown that emphasizing positive stereotypes and images of aging can weaken the negative influences of a situation on the behavior of older adults. For example, Hess et al [19] compared implicit and explicit priming of aging stereotypes on older adults' memory performance and found that those primed implicitly showed significant differences in memory, with positive primes showing greater recall than negative primes. To highlight the heightened effect of domain-specific stereotypes on cognitive and physical outcomes in older adults, Levy and Leifheit-Limson [20, page 230] found that when the age stereotype matched the outcome domain there was a stronger effect on performance, suggesting that when stereotype matching occurs "it is more likely to generate expectations that become self-fulfilling prophecies."…”
Section: How Stereotypes Work To Affect Healthmentioning
confidence: 99%
“…Por exemplo, estes estudos mostraram que, quando os participantes idosos são "primados" (i.e., participam numa tarefa de primação) implicitamente com atributos estereotípicos positivos do grupo das pessoas idosas têm melhores desempenhos em vários domínios do que quando são primados com atributos estereotípicos negativos. Este efeito tem sido estudado, por exemplo, nos desempenhos ao nível de testes de memória (Hess, Hinson, & Statham, 2004;Levy, 1996;Stein, Blanchard-Fields, & Hertzog, 2002). No entanto, o mesmo já tem sido demonstrado para outros domínios, inclusivamente em comportamentos que operam sem controlo consciente, como a caligrafia (Levy, 2000), os níveis de stresse na realização de tarefas exigentes (Levy, Hausdorff, Hencke, & Wei, 2000) e em medidas tão fundamentais como a vontade de viver (Levy, Ashman, & Dror, 1999.…”
Section: Introductionunclassified
“…No entanto, o mesmo já tem sido demonstrado para outros domínios, inclusivamente em comportamentos que operam sem controlo consciente, como a caligrafia (Levy, 2000), os níveis de stresse na realização de tarefas exigentes (Levy, Hausdorff, Hencke, & Wei, 2000) e em medidas tão fundamentais como a vontade de viver (Levy, Ashman, & Dror, 1999. Um aspecto central desta pesquisa é a de que estes efeitos não ocorrem nos jovens pelo que os autores salientam, o papel da relevância para as pessoas idosas dos estereótipos que estão a ser primados (Hess et al, 2004). Ou seja, as pessoas processam constantemente a informação à sua volta por referência a si próprias, tornando as categorias associadas ao seu auto-conceito muito mais facilmente acessíveis (Shih, Ambady, Richeson, Fujita, & Gray, 2002).…”
Section: Introductionunclassified